Food process engineering and technology - Berk, Zeki (Amsterdam, Academic Press, 2013)
"The last thirty years have seen the establishment of Food Engineering both as an academic discipline and as a profession. Combining scientific depth with practical usefulness, this book serves as a tool for graduate students as well as practicing food engineers, technologists and researchers looking for the latest information on transformation and preservation processes as well as process control and plant hygiene topics."--publisher's website.
1. Physical properties of food materials -- 2.Fluid flow -- 3. Heat and mass transfer -- 4. Reaction kinetics -- 5. Elements of process control -- 6. Size reduction -- 7. Mixing -- 8. Filtration and expression -- 9. Centrifugation -- 10. Membrane processes -- 11. Extraction -- 12. Adsorption and ion exchange -- 13. Distillation -- 14. Crystallization and dissolution -- 15. Extrusion -- 16. Spoilage and preservation of foods -- Thermal processing -- 18. Thermal processes, methods and equipment -- 19. Refrigeration: chilling and freezing -- 20. Refrigeration -- 21. Evaporation -- 22. Dehydration -- 23. Freeze drying (lyophilization) and freeze concentration -- 24. Frying, baking, roasting -- 25. Chemical preservation -- 26. Ionizing irradiation and other non-thermal preservation processes -- 27. Food packaging -- 28. Cleaning, disinfection, sanitation.
Previously published in 2009.
Includes bibliographical references and index.
Keywords: Food industry and trade -- Technological innovations; Food processing plants